Software Development Practices and Tools for University-Industry R&D projects - Cruz, Dhyego Tavares; Almeida, Erlon Pereira; Santos Junior, Jander Pereira; Paixão, Felipe de Sant’Anna; Santana Junior, Enio Garcia de; Souza, Rodrigo Rocha Gomes e; Iwamoto, Hérsio Massanori; Durão, Frederico Araújo; Prazeres, Cássio Vinicius Serafim; Machado, Ivan do Carmo; Figueiredo, Gustavo Bittencourt; Peixoto, Maycon Leone Maciel; et al. (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2024)
Research and development (R&D) projects involving universities and industry drive innovation by bringing scientific knowledge closer to practical problems. Nevertheless, the partnership comes with challenges, such as high developer turnover, team members with diverse backgrounds and experience levels, and part-time contributors. In this paper, we report experiences in a large R&D project in the smart home field, in which we proposed software development practices and tools with the goal of promoting short feedback cycles and dissemination of best practices. By surveying the developers of this project, we discovered that the practices and tools were generally well accepted and also determined specific areas that need improvement. The insights collected in this study can be used by other teams conducting R&D projects.